PENGARUH SUHU, WAKTU, DAN KADAR AIR PADA PIROLISIS PELEPAH KELAPA SAWIT (Jurnal Teknik Kimia USU, 2017)
Palm plantations in Indonesia began to grow rapidly since the early 80s. The area of ​​Indonesia's oil palm in 2013 was 10.4 million ha and increased 4.69% annually. The production of palm midrib was about 22 midribs per tree per year with the weight of midrib meat ranging from 2.2 kg. The palm midrib is composed of cellulose, hemicellulose, and lignin, which can be used as liquid smoke. The purpose of this study was to analyze the effect of temperature and time of pyrolysis on the yield and quality of liquid smoke produced. The pyrolysis process of fractured palm was performed at 150 ºC, 200 ºC, and 250 ºC for 30 minutes, 60 minutes, 90 minutes. The results indicated that the yield of liquid smoke tends to decrease with increasing pyrolysis temperature, and tends to increase with increasing pyrolysis time in which the difficult condensed gas production increases with increasing temperature and time of pyrolysis. The highest yield of liquid smoke pyrolysis temperature of 150 OC with pyrolysis time 120 minutes that is equal to 43.47%. In this study, obtained the best results for a pH value of 3.1 is done at process temperatures of 250 ° C with processing time 60 minutes